Evaluating urban micrometeorites as a research resource—A large population collected from a single rooftop. (27th July 2021) - Suttle, M. D.; Hasse, T.; Hecht, L.
Abstract: We report the recovery and characterization of a new urban micrometeorite collection derived from the rooftop of an industrial building in Germany. We identified 315 micrometeorites (diameter: 55–515 µm, size peak: ˜150 µm, size distribution slope exponent: −2.62). They are predominantly S‐type cosmic spherules (97.2%) but also two G‐type spherules (0.6%), an unmelted coarse‐grained single‐mineral micrometeorite, and eight scoriaceous particles (2.5%) or particles transitional between scoriaceous micrometeorites and porphyritic spherules. Their analysis details how the magnetite rim on partially melted micrometeorites is progressively diluted as the melt fraction increases during heating. At least 10 micrometeorites contain platinum group nuggets (PGNs). They have chondritic compositions but are depleted in volatile Pd. However, a single nugget preserves chondritic Pd concentrations. We suggest that an Fe‐Ni‐S bead originally containing the PGN escaped its host cavity and wet the particle exterior, creating an Fe‐rich melt that protected the nugget from evaporation. This melt layer oxidized forming magnetite—indicating that wetting events can affect the texture and composition of micrometeorites. Utilizing the well‐constrained surface area (8400 m 2 ) and rooftop age (21 yr), we attempted the first global mass flux estimate based on urban micrometeorite data. This produced anomalously low values (13.4 t yr –1 ), even when correcting for losses due to sample processing (<89.7 t yr –1 ). Our value is approximately two orders of magnitude lower than previous estimates, indicating that >99% of particles are missing, having been lost via drainage and cleaning. Rooftop collection sites have limited potential for mass flux calculations unless problems of loss can be resolved. However, urban micrometeorite collections have other advantages, notably exceptionally well‐preserved particles with extremely young terrestrial ages and the ability to extract many micrometeorites from accessible sites. Urban micrometeorites should be considered complementary to Antarctic and deep‐sea collections with potential for citizen science and educational exploitation.